Organoleptic test analysis and effect of liquid smoke concentration on smoked fish. (November 2019) - Hadanu, Ruslin; Lomo, Christine P.
Abstract: Fish Liquid smoke is one of the food products are preferred by Indonesian society in general and in particular Maluku region. This study aims to analyzeorganoleptic, TPC, Fat Content, Total Acid, Total Protein, Total Molds, Phenol levels to Concentration of Liquid Smoke Fish. The research method descriptions experimental concentration of 1% and 3% and smoked fish. Organoleptic analysis has a high degree of pleasure in the taste of liquid smoke 2430 codes with a value of 2.90, smell on code 2430. For textures in code 2430, 2437, 2438 with a value of 2.70, and the color in code 2438 was received by the panelist. The results of Total Plate Count (PLT) inhibit microbial growth at a concentration of 3% for 30 minutes soaking time, analysis of total acid levels at a concentration of 3% (57.6%). The highest total protein level (23.05%) concentration of 1%, analysis of total molds at a concentration of 1%, and analysis of phenol at a concentration of 3% have the highest phenol content of 4.06%.